2011
DOI: 10.1148/radiol.11090563
|View full text |Cite
|
Sign up to set email alerts
|

Early Diagnosis of Ovarian Carcinoma: Is a Solution in Sight?

Abstract: http://radiology.rsna.org/lookup/suppl/doi:10.1148/radiol.11090563/-/DC1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 132 publications
2
81
0
7
Order By: Relevance
“…In addition, we found that CT could detect adnexal masses quite successfully, with a 93% sensitivity and a 70% specificity, as is consistent with previous reports, but it does not show sufficient sensitivity and specificity to determine local tumor dispersion like uterine and tubal involvement, pelvic fat plan obliteration and bladder metastases [5,19,20]. As it has been suggested before, we think MRI may yield more useful results regarding these areas [21,22].…”
Section: Discussionsupporting
confidence: 86%
“…In addition, we found that CT could detect adnexal masses quite successfully, with a 93% sensitivity and a 70% specificity, as is consistent with previous reports, but it does not show sufficient sensitivity and specificity to determine local tumor dispersion like uterine and tubal involvement, pelvic fat plan obliteration and bladder metastases [5,19,20]. As it has been suggested before, we think MRI may yield more useful results regarding these areas [21,22].…”
Section: Discussionsupporting
confidence: 86%
“…The system was able to differentiate normal postmenopausal versus malignant postmenopausal (P = .0237) ovaries, with sensitivity and specificity of 83% and 83%, respectively, while no significant differences were found between normal premenopausal versus normal postmenopausal (P = .2361) ovaries (Fig 9). The group (113,114) later reported of ovarian cancer are ineffective, with poor sensitivity and specificity (110). A large randomized multicenter clinical trial (111) performed in the United States to determine the effect of screening on ovarian cancer mortality concluded that simultaneous screening with CA-125 (serum biomarker for ovarian cancer) and transvaginal US did not reduce ovarian cancer mortality when compared with usual care.…”
Section: Review: Photoacoustic Imaging In Oncologymentioning
confidence: 99%
“…On the other hand, early-and middle-stage ovarian cancer is rarely detected due to the lack of reliable tools and biomarkers (Lutz et al, 2011). Even for the advanced-stage disease, being short of sensitive biomarkers has become a big obstacle for the estimate of intervention therapies and the monitoring of metastatic tumor tissue.…”
Section: Introductionmentioning
confidence: 99%